Facial flow line and its effect on dental midline deviation on a female subject in an Asian population - A cross-sectional study - Muhammad Maaz; Kanza Tahir; Mubassar Fida; Rashna H Sukhia (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: This study aims to understand the relationship between midline deviations and the inherent asymmetry that can be observed in a human face. MATERIALS AND METHODS: A cross-sectional study was conducted using a frontal smile photograph of a female which was altered on Adobe Photoshop software version 23.0 into eight different photographs by deviating the dental midlines by 2 mm, 4 mm, and 6 mm towards and away from the facial flow line (FFL). 4 mm of chin deviation was incorporated in all the pictures except for the first picture in which the midline and chin were kept symmetric. Orthodontic residents evaluated those photographs on an interrupted visual analogue scale (VAS) with 0 being the least attractive and 10 being the most. Simple linear regression was applied to observe factors associated with VAS score. RESULTS: Highest score was observed for picture with midline and chin on (MLCon) with a score of 9.4 ± 0.7, followed by picture with midline on and chin deviated (MLon) 8.7 ± 0.8. The deviations towards green zone received higher scores in comparison to deviations towards red zone. Linear regression revealed highly statistically significant differences between the constant and the rest of the pictures. CONCLUSIONS: The formation of green and red zones by the FFL influences the perception of midline deviation as judged by orthodontic residents. Midline when deviated towards the green zone, was judged to be more aesthetic than when shifted towards the red zones.